Yugoslav Architecture between the Two World Wars (1918-1941): Contexts of Interpretations - Jelena Gačić Ivanov (Prostor)
Many years of productive research by Prof. Dr. Aleksandar Kadijević on the phenomenological aspects of the interwar architecture of the Kingdom of SHS / Yugoslavia as a state unit have been layered and systematized in the monograph “Yugoslav Architecture between the Two World Wars (1918-1941): Contexts of Interpretation”. The content consists of ten chapters, or essays, with a conclusion or an epilogue, aimed at deepening the discussion and research perspectives of the period in question.